Enrollment on clinical trials does not improve survival for children with acute myeloid leukemia: A population‐based study. Issue 20 (6th October 2018) - Truong, Tony H.; Pole, Jason D.; Barber, Randy; Dix, David; Kulkarni, Ketan P.; Martineau, Emilie; Randall, Alicia; Stammers, David; Strahlendorf, Caron; Strother, Douglas; Sung, Lillian
Abstract : Background: It is questionable whether enrollment on clinical trials offers any survival advantage at the population level over standard‐of‐care treatment. The objectives of this study were to describe the impact of trial enrollment on event‐free survival and overall survival in pediatric acute myeloid leukemia (AML) using the Cancer in Young People in Canada (CYP‐C) database. Methods: Children were included if they had had AML newly diagnosed between ages birth and 14 years from 2001 to 2012. CYP‐C is a national pediatric cancer population‐based database that includes all cases of pediatric cancer diagnosed and treated at 1 of the 17 tertiary pediatric oncology centers in Canada. Univariate and Cox proportional hazards models were used to evaluate the impact of initial trial enrollment on survival. Results: In total, 397 eligible children with AML were included in the analysis, of whom 94 (23.7%) were enrolled on a clinical trial at initial diagnosis. The most common reason for non‐enrollment was that no trial was available. The event‐free survival rate at 5 years was 57.8% ± 5.2% for those enrolled versus 54.8% ± 2.9% for those not enrolled ( P = .75). The overall survival rate at 5 years was 70.1% ± 4.9% for those enrolled versus 66.3% ± 2.8% for those not enrolled ( P = .58). Enrollment on a trial was not associated with improved event‐free or overall survival in multiple regression analyses. Conclusions: Enrollment on a clinical trial was not associated with improved survival for children with AML in a population‐based cohort. Rationale for trial enrollment should not include the likelihood of benefit compared with non‐enrollment. Abstract : By using the Cancer in Young People in Canada database, children with newly diagnosed acute myeloid leukemia are studied to determine whether clinical trial enrollment has any effect on survival. In this population‐based cohort of children with acute myeloid leukemia, enrollment on a clinical trial is not associated with improved survival. See also pages3965‐8 and4064‐71 .